Comparison of Performance on the Clock Drawing Test Using Three Different Scales in Dialysis Patients - Taim Abdullah Muayqil; Ahmad Raed Tarakji; Abdullah Mohammad Khattab; Nasser Talal Balbaid; Ahmad Mohedeen Al-Dawalibi; Sami Ahmed Alqarni; Reema Ali Hazazi; Mohammed H. Alanazy (Behavioural Neurology)
Background. The clock drawing test (CDT) is frequently used to detect changes in cognition. Multiple scales of varying length have been published to assess performance. The aim of this study is to compare the CDT performance measured by three scales among a sample of nondemented patients on renal dialysis and identify the variables that affect performance. Methodology. This is a cross-sectional study performed at the dialysis unit at King Saud University Medical City. Eighty-nine dialysis patients performed the CDT. The CDT was scored by the methods of Rouleau et al. (RCS 10-point), Babins et al. (BCS 18-point), and the MoCA (MCS 3-point). Regression models were used to determine influencing demographic and dialysis variables. Scores were then correlated, and a combined factor analysis of scale components was done. Results. Females represented 44.6%, the mean (SD) age was 49.99 (15.49) years, and education duration was 10.29 (5.5) years. Dialysis vintage was 55.81 (62.91) months. The scores for the MCS, RCS, and BCS were 2.18 (1.08), 6.67 (3.07), and 11.8 (5.5), respectively, with significant correlation (P<0.0001). In all scales, increasing age was associated with a lower score (each P<0.0001). The scores increased with increasing education (each P<0.0001). Diabetics had a lower score on both the BCS and MCS by 2.56 (SE 1.2) (P=0.035) and 0.71 (P=0.003) points, respectively. However, only age and years of education were significant in the multivariable analysis. In factor analysis, two shared factors appeared between the three scales: hand and number placement and the clock face. Conclusion. Age and education influence the performance on the CDT, and factors diverged into executive and visuospatial components. The MCS is likely to yield useful information but should be interpreted as part of the MoCA.